دور التربية البدنية و الرياضية في الحد من تنامي ظاهرة العنف في الوسط المدرسي دراسة ميدانية على عينة من تلاميذ السنة رابعة متوسط لبعض متوسطات مدينة بسكرة - فريجـــــة, أحمـــــد; زروق, ياسمينة (University of Eloued جامعة الوادي, 2016)
تعتبر التربية البدنية و الرياضية جزءا اساسيا من التربية العامة فقد لقيت اهتماما واضحا في العصر الحديث و ذلك ادراكا لقيمتها في حياة المجتمعات ، ولضرورتها لنمو و تطور الافراد، فمن بين اهداف التربية تنشئة الفرد تنشئة سليمة و متكاملة تشمل مختلف الجوانب الجسمية و العقلية و الوجدانية ليتعايش الفرد مع مجتمعه و يتكيف مع المحيطين به ، وباعتبار مادة التربية البدنية و الرياضية جزء لا يتجزأ من الاطار العام لمناهج المنظومة التربوية ، لكونها مادة دراسية لها اهدافها المسطرة والمراد تجسيدها في شعور و سلوك الناشئة، فحصة التربية البدنية و الرياضية تعد احدى الفضاءات الحيوية التي تستهدف بشكل مباشر احداث التوازن في شخصية التلميذ، فمن خلالها يتم تفريغ كل الشحنات السالبة و الطاقة المكبوتة نتيجة ضغط الاسرة و المدرسة على حد سواء، فممارسة النشاطات الرياضية هي بمثابة علاج للعديد من المشكلات التي يعاني منها التلميذ كالخجل و الانطواء و العزلة ،وبالتالي هي تساعده على تلبية حاجاته ، البدنية، النفسية، الاجتماعية، و المعرفية ، مما يسهم في ازالة توتراته النفسية و السلوكية العنيفة Physical education and sports are an integral part of public education which have received a clear interest in the modern era because of their importance and the awareness of their value in the life of communities. Among the goals of Education is the upbringing of the individual and the upbringing of healthy which include various physical and mental and emotional aspects which lead the individual to live with his society and adopt to those around him. As physical and sports education material integral part of the educational system part, and academic subject has its goals that intended to teach the student's general educational principles and in particular course of physical education and sports is one of the curriculum tuition, which directly affect the educational process at the level of educational institutions, and through which offload all the negative charges and pent-up energy. As a result of family pressure and school alike, practice of sports activities is a treat for many of the problems afflicting the pupil who is shy introverted and isolated, etc. Therefore, it is to help him to meet his needs, physical, cognitive, psychological and social, as it removes the psychological tensions and violent behaviors
The role of physical education and sports in the reduction of the growing phenomenon of violence in schools A field study on a sample of students of the fourth year, the average of some of the averages of the city of Biskra
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: التربية البدنية و الرياضية، حصة التربية البدنية و الرياضية، العنف في الوسط المدرسي; Physical education and sports, the share of physical education and sports , violence in the school setting